Early Neurological Deterioration During Alteplase Infusion for Acute Ischemic Stroke: An Uncommon Complication of Intravenous Thrombolysis. Issue 3 (May 2017) - Safouris, Apostolos; Kargiotis, Odysseas; Magoufis, Georgios; Katsanos, Aristeidis H.; Stamboulis, Eleftherios; Tsivgoulis, Georgios
Abstract : Introduction: Recognizing new-territory ischemic stroke as an uncommon complication of intravenous thrombolysis is very important as it can lead to neurological deterioration during tissue-plasminogen-activator infusion. Case Report: We report a case of an 80-year-old patient that has been treated with intravenous thrombolysis for right middle cerebral artery acute ischemic stroke. During infusion he had an abrupt neurological deterioration that proved to be a distal embolization of an asymptomatic non-occluding tip-of-the-basilar thrombus to the territory of left posterior cerebral artery that has been missed by the treating neurologist and radiologist in the pretreatment computed tomography angiography. In the thrombectomy that followed, only the right carotid artery has been catheterized and only the right middle cerebral artery was successfully recanalized, leaving the left posterior cerebral artery occlusion untreated. Conclusions: This case highlights that the use of thrombectomy in clinical practice provides an effective therapeutic option for large vessel occlusion in this setting. However, high clinical suspicion for this rare complication is mandatory to proceed to correct diagnosis and treatment.